Linear dichroism of visible-region chromophores using M13 bacteriophage as an alignment scaffold. Issue 52 (20th August 2018) - Tridgett, Matthew; Moore-Kelly, Charles; Duprey, Jean-Louis H. A.; Iturbe, Lorea Orueta; Tsang, Chi W.; Little, Haydn A.; Sandhu, Sandeep K.; Hicks, Matthew R.; Dafforn, Timothy R.; Rodger, Alison
Abstract : Here we characterise four dyes and assess the complementarity of linear dichroism and FRET in biomimetic light-harvesting antennae optimisation. Abstract : It is a challenge within the field of biomimetics to recreate the properties of light-harvesting antennae found in plants and photosynthetic bacteria. Attempts to recreate these biological structures typically rely on the alignment of fluorescent moieties via attachment to an inert linear scaffold, e.g. DNA, RNA or amyloid fibrils, to enable Förster resonance energy transfer (FRET) between attached chromophores. While there has been some success in this approach, refinement of the alignment of the chromophores is often limited, which may limit the efficiency of energy transfer achieved. Here we demonstrate how linear dichroism spectroscopy may be used to ascertain the overall alignment of chromophores bound to the M13 bacteriophage, a model linear scaffold, and demonstrate how this may be used to distinguish between lack of FRET efficiency due to chromophore separation, and chromophore misalignment. This approach will allow the refinement of artificial light-harvesting antennae in a directed fashion.